Douglas E. Trapp letter to Thomas H. Kent regarding raptor migration watch, October 3, 1986 - Trapp, Douglas E.et al (1986)
Douglas E. Trapp letter to Thomas H. Kent regarding a raptor migration watch at War Eagle Park in Sioux City, Iowa with field biologist Kevin J. Loftus. It includes other topics such as weather conditions and raptor migration patterns. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed